2019
DOI: 10.14738/assrj.610.7246
|View full text |Cite
|
Sign up to set email alerts
|

Generating and Allocating Internal Revenue for Public Secondary School Administration in Cross River State

Abstract: The design adopted for this study was correlation. Population of the study consisted of all the 504 public secondary schools principals in 18 LGAs in Cross Rivers State. However, purposive sampling technique was use to select the 504 principals a sample for the study. There were two research questions and two hypotheses formulated for the study. Questionnaire was the instrument used for data collection with 20 items and titled “Generation and Allocation of Internal Revenue for School Administration Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The traditional funding sources for the Nigerian tertiary education vary somewhat from point of view of the founding and proprietorship of the institutions. The federal tertiary institutions are funded by the federal government via grants for personnel costs, research funding and capital expenditures (Agunbiade & Dawud, 2017;Gebreyes, 2015;Nyeh & Kpee, 2019;Onuoha, 2013). It is on statutory note that federal tertiary institutions do not charge any tuition fees (Okojie, 2009) and it could be considered a serious violation for any federal tertiary institutions to impose tuition fees on the students or their parents (Ijaduola.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional funding sources for the Nigerian tertiary education vary somewhat from point of view of the founding and proprietorship of the institutions. The federal tertiary institutions are funded by the federal government via grants for personnel costs, research funding and capital expenditures (Agunbiade & Dawud, 2017;Gebreyes, 2015;Nyeh & Kpee, 2019;Onuoha, 2013). It is on statutory note that federal tertiary institutions do not charge any tuition fees (Okojie, 2009) and it could be considered a serious violation for any federal tertiary institutions to impose tuition fees on the students or their parents (Ijaduola.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study provided additional information to the current research that public secondary schools allow the private examination candidates to use the school library and laboratory and pay fees. Similarly, a quantitative study by Nyeh and Kpee (2019) in Nigeria reported that school income-generating activities include NGOs, school shops, fundraising, renting facilities, school alumni, and handcrafts as the primary sources of IGAs. Findings from studies conducted in Ghana and Nigeria revealed the income-generating activities; however, by considering technological and educational systems between Tanzania and Ghana as well as Nigeria.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The primary source of Nigerian tertiary education funding differs depending on the ownership of the institutions. The federal government is responsible for personnel and capital costs as well as research and development funds via several grants in federal tertiary institutions [15,33,34]. Statutorily, tertiary institutions owned by federal government are tuition free and it is considered serious violations if any federal tertiary institution charges any tuition fee [15,35].…”
Section: Introductionmentioning
confidence: 99%